Analisis Perbandingan Penghimpunan Dana Pihak Ketiga Bank Syariah Sebelum dan Sesudah Kebijakan Tax Amnesty - Johan, Tk. Umar; Muslikhati, Muslikhati (FALAH: Jurnal Ekonomi Syariah, 2018)
This study aims to reveal the comparison of Third Party Funds (DPK) of sharia bank as Bank Perception Tax Amnesty policy in 2016.This study used a comparative quantitative approach with the subject of research is the Third Party Funds of sharia bank the receiver of Tax Amnesty funds in 2016. The selection of DPK as a research setting based on the existence of funds for bank is vital for business continuity, because without sufficient funds the bank will not be function properly. The determination of samples was decided by Ministry of Economic in Republic Indonesia No.600/KMK.03/2016, so the sample of this research compare within 3 banks, those are; Bank Muamalat Indonesia, Bank Negara Indonesia Syariah, and Bank Syariah Mandiri. The test equipment used Paired Sample T-Test assisted software SPSS 21. The result of Paired Sample T-Test founded that there was Î± Â P value t equal to 0,000 or< 0,05, means a significant difference of DPK accumulation before and after Tax Amnesty policy in 2016. The average of DPK sharia bank before Tax Amnesty policy accumulated Rp 124,1 Trillion and increased Rp 132,9 Trillion after Tax Amnesty policy.